La relative originalité de l'Accord Canada-Peru de coopération dans le domaine du travail - Verge, Pierre (Relations industrielles / Industrial Relations, 2008)
Analyzes the distinctive features of the Canada-Peru trade agreement in the context of accords with other nations.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z